2015
DOI: 10.1039/c5ta04930j
|View full text |Cite
|
Sign up to set email alerts
|

A facile strategy for the fabrication of a bioinspired hydrophilic–superhydrophobic patterned surface for highly efficient fog-harvesting

Abstract: Fog water collection represents a meaningful effort in the places where regular water sources, including surface water and ground water, are scarce. Inspired by the amazing fog water collection capability of Stenocara beetles in the Namib Desert and based on the recent work in biomimetic water collection, this work reported a facile, easy-to-operate, and low-cost method for the fabrication of hydrophilic-superhydrophobic patterned hybrid surface toward highly efficient fog water collection. The essence of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
119
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 178 publications
(124 citation statements)
references
References 49 publications
(84 reference statements)
5
119
0
Order By: Relevance
“…Finally, with a fixed pressure on the top of materials and a pre‐setting temperature heating in an oven, the two materials were merged. It was found that the samples with the gauze of 50 and treated at 130 °C exhibited the best fog‐collecting ability in a homemade fog‐collecting system due to its optimal hydrophilic‐super‐hydrophobic patterned surface …”
Section: The Fabrication and Further Fundamental Research Of Bionic Wmentioning
confidence: 99%
“…Finally, with a fixed pressure on the top of materials and a pre‐setting temperature heating in an oven, the two materials were merged. It was found that the samples with the gauze of 50 and treated at 130 °C exhibited the best fog‐collecting ability in a homemade fog‐collecting system due to its optimal hydrophilic‐super‐hydrophobic patterned surface …”
Section: The Fabrication and Further Fundamental Research Of Bionic Wmentioning
confidence: 99%
“…24 The rGO membrane sample (2.5 cm × 2.5 cm) was fixed on a glass substrate with the same size. The sample was hung with its surface perpendicular to the horizontal plane.…”
Section: Fog Harvesting Experimentsmentioning
confidence: 99%
“…Copyright 2007 American Chemical Society); (b) hydrophilic steel needles pierced through superhydrophobic film (adapted with permission from [27]. Copyright 2015 American Chemical Society); (c) superhydrophobic copper mesh pressed into hydrophilic (relative to the copper mesh) polymer sheet [28]; and (d) dewetted hydrophilic polymer regions atop a hydrophobic (relative to the hydrophilic polymer regions) polymer (adapted with permission from [29]. Copyright 2015 American Chemical Society).…”
Section: Stipagrostis Sabulicola (Grass)mentioning
confidence: 99%